The challenge of originalism : theories of constitutional interpretation - Huscroft, Grant; Miller, Bradley W. (Bradley Wayne), 1968- (Cambridge, UK. : Cambridge University Press, 2011)
'Originalism is a force to be reckoned with in constitutional interpretation. At one time a monolithic theory of constitutional interpretation, contemporary originalism has developed into a sophisticated family of theories about how to interpret and reason with a constitution. Contemporary originalists harness the resources of linguistic, moral, and political philosophy to propose methodologies for the interpretation of constitutional texts and provide reasons for fidelity to those texts. The essays in this volume, which includes contributions from the flag bearers of several competing schools of constitutional interpretation, provides an introduction to the development of originalist thought, showcases the great range of contemporary originalist constitutional scholarship, and situates competing schools of thought in dialogue with each other. They also make new contributions to the methodological and normative disputes between originalists and non-originalists, and among originalists themselves'--
Includes bibliographical references and index.
Keywords: Constitutional law -- Philosophy; Law -- Interpretation and construction; Origin (Philosophy)